Measurements of top-quark pair to Z-boson cross-section ratios at √s = 13; 8; 7 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2017)
Ratios of top-quark pair to Z-boson cross sections measured from proton-proton collisions at the LHC centre-of-mass energies of √s = 13TeV, 8TeV, and 7TeV are presented by the ATLAS Collaboration. Single ratios, at a given √s for the two processes and at different √s for each process, as well as double ratios of the two processes at different √s, are evaluated. The ratios are constructed using previously published ATLAS measurements of the t¯t and Z-boson production cross sections, corrected to a common phase space where required, and a new analysis of Z → ℓ+ℓ- where ℓ = e,μ at √s = 13TeV performed with data collected in 2015 with an integrated luminosity of 3.2 fb-1. Correlations of systematic uncertainties are taken into account when evaluating the uncertainties in the ratios. The correlation model is also used to evaluate the combined cross section of the Z → e+e- and the Z → μ+μ- channels for each √s value. The results are compared to calculations performed at next-to-next-to-leading-order accuracy using recent sets of parton distribution functions. The data demonstrate signi cant power to constrain the gluon distribution function for the Bjorken-x values near 0.1 and the lightquark sea for x < 0.02